Joint knowledge generation in European R&D networks: Results from a discrete choice modelling perspective - Florian Reinold; Manfred Paier; Manfred M. Fischer (European Regional Science Association (ERSA), 2012)
The objective of this study is to explore the determinants of joint knowledge generation within European networks of R&D collaboration. This study distinguishes between two types of joint knowledge generation: scientific and commercially relevant knowledge generation. Joint generation of scientific knowledge is measured by co-authored scientific publications, while joint commercially relevant knowledge is measured by co-owned patents and artefacts. Unit of analysis are dyads of organisations jointly participating in projects of the 5th EU Framework Programme (FP5). The data for carrying out this study is taken from a survey among FP5 participants and the EUPRO database. 23 EU member countries (Bulgaria, Cyprus, Malta and Rumania are excluded) plus Switzerland and Norway are included. Regression methods for discrete choice (logit and probit) are employed to meet the objective. The independent variables taken into consideration encompass the types of organisations involved in the dyad, geographical and cultural obstacles, relational factors and project characteristics. Results show that dyads involving universities have the highest probability not only to jointly generate scientific knowledge but also to jointly generate commercially relevant knowledge, whereas the involvement of an industry organisation results in a low probability for both types of knowledge generation. Perhaps, this can be attributed to the fact that joint knowledge generation entails disclosure of own knowledge, which is actually a task of universities but is problematic for industry organisations. Another important result is that crossing national border has a significant positive rather than negative effect on joint scientific knowledge generation, which is essentially a consequence of how the Framework Programmes had been set up. Similarly, crossing EU-15 external border has a positive effect on joint knowledge generation, indicating that the FPs work well in achieving their aim of supporting the catching up process of CEE countries. But, joint generation of commercially relevant knowledge is negatively influenced by language borders. This can be explained by the fact that the co-development of patentable knowledge or artefacts requires more intensive and complex interactions than to co-author a scientific publication where English is the lingua franca anyway. Results on relational factors and project characteristics satisfy expectations: Duration of collaboration and the existence of previous collaboration have a positive effect on joint knowledge generation, whereas the project size, measured by number of participants, affects joint knowledge generation negatively.
Keywords: 330